Willingness to pay for protected areas: A case of Etna Park. (October 2018) - Platania, Marco; Rizzo, Marcella
Highlights: Protected areas and parks are places (models, laboratories…) of sustainable development. Natural parks are tourist destinations increasingly visited (by both Italian and foreign visitors). Governance is fundamental for effective management of tourist use. In the case study, the WTP of a ticket is higher for young people and foreign tourists. In the case study, the introduction of a modest tax should not cause a reduction in tourist demand. Abstract: Protected areas represent spaces of great environmental and social value. Their good management can allow both the protection of biodiversity and the growth of tourists' interest. With regard to the governance of these areas, the possibility of charging visitors for their enjoyment is frequently discussed. This problem is very pertinent in Sicily (Italy) where the government of the region has recently decided to introduce an entry ticket for some regional protected areas. Among the protected areas of Sicily, the Etna Volcano park is an area with extraordinary natural and cultural features and a major tourist attraction whose value has recently been recognized by UNESCO. The objective of this study is to evaluate the willingness of visitors to pay (WTP) an admission ticket for the Etna Park. After some reflections on the importance of protected areas, the results of a survey analyzing the visitors' impression and their opinions about the possible introduction of an access ticket to the Park are presented. The results obtained provide useful facts to support decision makers with regard to the choice and the relative value of a ticket.